2017
DOI: 10.1504/ijict.2017.081003
|View full text |Cite
|
Sign up to set email alerts
|

Virtual teamwork training: factors influencing the acceptance of collaboration technology

Abstract: Abstract:The purpose of this study was to identify the factors that influence the acceptance of electronic collaboration technology by higher education students and that influence their predicted usage of the technology for virtual team collaboration. The research combined the unified theory of acceptance and usage of technology (UTAUT) with a virtual team-training model. All 108 participants completed a survey following their participation in virtual team 6 J. Godin et al.training. Ten hypotheses were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
9
1
1
Order By: Relevance
“…The development of hypotheses H1, H2, and H3 was supported by [46], where the constructs of PE, EE and SI were used to investigate the acceptance (BI) of the respondents to their virtual team framework in a learning environment. In [47], it was reported that the attitude towards the intention to use could be influenced by SI and FC, where FC was seen to be instrumental in empowering the individuals to have positive acceptance of the technology.…”
Section: B Development Of Unified Theory Of Acceptance Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of hypotheses H1, H2, and H3 was supported by [46], where the constructs of PE, EE and SI were used to investigate the acceptance (BI) of the respondents to their virtual team framework in a learning environment. In [47], it was reported that the attitude towards the intention to use could be influenced by SI and FC, where FC was seen to be instrumental in empowering the individuals to have positive acceptance of the technology.…”
Section: B Development Of Unified Theory Of Acceptance Frameworkmentioning
confidence: 99%
“…The work by [46] explored acceptance towards virtual teams but focused more on the learning environment using the UTAUT. The author in [46] investigated variables PE, EE, SI and FC towards the BI.…”
Section: Referring To the Benchmark Value Shown In Table V And Thementioning
confidence: 99%
“…PTTTĐT được đề cập trong các tài liệu bằng nhiều thuật ngữ khác nhau, như "công nghệ cộng tác" (Santillan & Horwitz, 2016;Solomon, 2016), "công nghệ cộng tác và truyền thông/giao tiếp điện tử", "CNTT và truyền thông/giao tiếp" (Dube & Marnewick, 2016), "công nghệ truyền thông/giao tiếp thông qua máy tính trung gian" (Lipnack & Stamps, 2000), "công nghệ truyền thông/giao tiếp" (Chaves et al, 2016), "công nghệ ảo" (Greer, Luethge, & Robinson, 2017), "CNTT" (Griffith, Sawyer, & Neale, 2003) hay "công nghệ" nói chung (Wise, 2016)… Nhiều bằng chứng cho thấy trong đội ảo, việc tương tác gián tiếp thông qua công nghệ sẽ dẫn đến nhiều hệ lụy về mặt xã hội như sự hiểu lầm, tổn thương, xung đột, tranh giành quyền lực, thiếu tin cậy… (Ebrahim, Ahmed, & Taha, 2011;Kayworth & Leidner, 2002;Ocker & Fjermestad, 2008). Bên cạnh đó, đôi khi đội ảo đòi hỏi ứng dụng PTTTĐT phức tạp (Bergiel, Bergiel, & Balsmeier, 2008), không phù hợp thói quen, không làm thành viên đội hài lòng, vì vậy họ không có ý định sử dụng, không chấp nhận ngay từ đầu hoặc giảm sử dụng theo thời gian (Godin et al, 2017). Ozcelik (2010) cho rằng nếu nhà quản lý không cung cấp cơ chế hỗ trợ đầy đủ, khi việc sử dụng công nghệ gặp sự cố, các thành viên đội ảo có thể phải ngừng việc.…”
Section: đặT Vấn đềunclassified
“…Previous studies have used the T‐TAQ questionnaire to evaluate team training with interprofessional students (Chen et al., 2019; Welsch et al., 2018), nursing students (Gaston, 2018; Godin et al., 2017; LaMothe et al., 2016; Maguire et al., 2015) and healthcare professionals (Grapensteter, 2017; Vertino, 2014). Bachelor's students are a different population from experienced healthcare professionals with respect to knowledge, teamwork and healthcare experience.…”
Section: Introductionmentioning
confidence: 99%